Isolation and characterization of pathogenic Klebsiella pneumoniae strains from lettuce: a potential source of antibiotic resistance and development of a mathematical model for ANOVA results - Khan, Ruby; Wali, Saima; Khan, Sumbal; Munir, Shaista; Pari, Bakht; Yousuf, Amjad M.; Almutawif, Yahya A. (Frontiers in Microbiology, 2024)
This study aimed to evaluate the prevalence of Klebsiella pneumoniae contamina- tion specifically in raw lettuce from Risalpur, Pakistan, and to analyze the antibiotic susceptibility profiles of the isolated strains. Lettuce samples were collected from vari- ous sources and screened for the presence of K. pneumoniae. Our findings indicate a significant prevalence of K. pneumoniae in lettuce, highlighting considerable public health risks associated with inadequate hygiene practices, improper transportation and storage conditions, and the use of contaminated irrigation water. Antimicrobial susceptibility testing revealed that the isolated strains exhibited high susceptibility to gentamicin, while resistance was notably observed against doxycycline, vancomycin, and ticarcillin. The identification of multidrug-resistant (MDR) strains underscores the urgent need for improved antibiotic stewardship in the management of foodborne pathogens. To assess the effectiveness of antibiotics, ANOVA was performed to identify signi- ficant differences in inhibition zones among different antibiotics. Subsequently, a linear regression model was utilized to predict the Zone of Inhibition based on antibiotic con- centrations, with model coefficients β0 = 10.6667 and β1 = 0.4556 representing the baseline Zone of Inhibition and the change in inhibition per unit increase in antibiotic concentration, respectively. This approach provided a comprehensive understanding of how varying antibiotic concentrations impact bacterial inhibition. In conclusion, the detection of Klebsiella pneumoniae in raw lettuce underscores the urgent need for enhanced food safety protocols and stringent hygiene practices throughout the food production chain. Addressing these concerns is crucial for mit- igating health risks and combating the growing challenge of antibiotic resistance in foodborne pathogens